Study Of Biostimulation Effect On Normal And Anaemic Human Blood Cell Irradiated By 589 nm And 532 nm Laser - Fauzi, Nabihah (2019)
Laser (light amplification by stimulated emission of radiation) is a monochromatic light. It has been widely used in various fields including in the field of medicine. Application of Low Level Laser (LLL) at low output power (1-500 mW) has been proven to have therapeutic or biostimulation effects on biological tissues or cells. Widespread applications of LLL in medical practices including blood irradiation have resulted in the investigations on the bio-stimulation effects on irradiated human red blood cell (RBC). In this study, full blood count was measured on normal and anaemic human blood, the morphology of RBC were compared and the adenosine 5’-triphosphate (ATP) values were analysed.